Ileostomy closure in an enhanced recovery setting. (October 2015) - Bracey, E.; Chave, H.; Agombar, A.; Sleight, S.; Dukes, S.; Bryan, S.; Branagan, G.
Abstract Aim Hospital stays of 5 days or more are not uncommon following ileostomy closure, yet within an enhanced recovery programme (ERP) it is possible for patients to be discharged on the first postoperative day following anterior resection. The aim of this study was to evaluate whether the introduction of an ERP for ileostomy closure reduced hospital stay without affecting morbidity or readmission rates. Method Consecutive patients undergoing elective ileostomy closure from October 2000 to March 2013 were included in this study. The data were collected prospectively into a database. Enhanced recovery was introduced for all elective ileostomy closures in June 2010. Demographic data, length of stay (LOS), readmission, morbidity and mortality were compared between the two groups using the Mann–Whitney U‐test and Fisher's exact test. Results One hundred and forty‐five patients underwent elective ileostomy closure during the study period (37 ERP and 108 pre‐ERP). There were no differences between the two groups with respect to demographics, American Society of Anesthesiologists grade, prior radiotherapy or chemotherapy, operative time, body mass index, antibiotic use or closure method. Readmission rates (5% vs 6.5%, P = 1.0), morbidity (8% vs 10%, P = 1.0) and mortality (0% vs 0%) were not significantly different. Median (2 vs 4 days, P < 0.0001) and mean (3.4 vs 5.6 days, P = 0.033) LOS were significantly shorter in the ERP group compared with the pre‐ERP group. Conclusion An ERP for closure of ileostomy significantly reduces LOS without adverse effects for patients.